Replacement of Green Fodder with Corn Silage: Effects on Nutrient Utilization, Antioxidant Status and Immune Response in Hariana Heifers - Verma, Ashwani Kumar; Kumar, Muneendra; Kumar, Vinod; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash; Shukla, Pankaj Kumar; Sirohi, Rajneesh (Indian Journal of Animal Nutrition, 2022)
The systemic concentrations of key blood metabolites associated with feed intake, growth, nutrient partitioning, and utilization are potential physiological markers of the dietary variation. The aim of this study was to determine the effect of green fodder replacement with corn silage on biomarkers of nutrient metabolism, antioxidant potential, and immune response in growing Hariana cattle. A total of 18 growing Hariana calves were randomly assigned into three groups (having 6 calves in each group) on body weight (130±3.0 kg) and age basis (14±1.5 months). Experimental heifers either received a basal diet devoid of corn silage (control) or were fed on TMR of which 50% (Silage50%) and 100% (Silage100%) green fodder (DM basis) were replaced with corn silage. In the present study, plasma total protein and albumin concentration showed higher (P0.05) effect of green fodder replacement with corn silage. The results of this study indicated that the replacement of green fodder with corn silage did not exert any adverse effect on the blood biomarkers of nutrient metabolism, antioxidant potential, and immune response therefore can be used as a substitute of green fodder in growing Hariana cattle.